Nexuses Between the Chemical Design and Performance of Small Molecule Dopant‐Free Hole Transporting Materials in Perovskite Solar Cells. Issue 11 (5th December 2022) - Khan, Danish; Liu, Xiaoyuan; Qu, Geping; Nath, Amit Ranjan; Xie, Pengfei; Xu, Zong‐Xiang
Abstract: Perovskite solar cells (PSCs) have grabbed much attention of researchers owing to their quick rise in power conversion efficiency (PCE). However, long‐term stability remains a hurdle in commercialization, partly due to the inclusion of necessary hygroscopic dopants in hole transporting materials, enhancing the complexity and total cost. Generally, the efforts in designing dopant‐free hole transporting materials (HTMs) are devoted toward small molecule and polymeric HTMs, where small molecule based HTMs (SM‐HTMs) are dominant due to their reproducibility, facile synthesis, and low cost. Still, the state‐of‐art dopant‐free SM‐HTM has not been achieved yet, mainly because of the knowledge gap between device engineering and molecular designs. From a molecular engineering perspective, this article reviews dopant‐free SM‐HTMs for PSCs, outlining analyses of chemical structures with promising properties toward achieving effective, low‐cost, and scalable materials for devices with higher stability. Finally, an outlook of dopant‐free SM‐HTMs toward commercial application and insight into the development of long‐term stability PSCs devices is provided. Abstract : It is requisite to develop dopant‐free hole transporting materials (HTMs) to avoid formidable engineering and instability in perovskite solar cells. Organic HTMs, especially small molecules are easily reproducible. While considering the stability and efficiencies of perovskite solar cells, this review reveals the role of different molecular design strategies applied to small molecule HTMs.